Antimicrobial activity of crude extract of Caryocar brasiliense, Morinda citrifolia, Annona muricata and Morus nigra on clinically important bacterial strains (Research, Society and Development, 2022)
The indiscriminate use of antibiotics brings with it several problems related to pharmacotherapy, one of these problems is bacterial resistance to the drug. Therefore, the present work had the general objective of the study was to analyze the antibacterial activity of the crude extract of Pequi flower (Caryocar brasiliense), None fruit (Morinda citrifolia), Graviola leaf (Annona muricata) and Blackberry leaf (Morus nigra) against clinically important bacterial strains. The antimicrobial activity was analyzed in an in vitro test, compared to the agar diffusion method with the well technique. All experiments were performed in triplicate. The results were statistically analyzed using the one-way ANOVA test and Dunnett's test. p values ≤ 0.05 were considered significant. The results showed that the extract of Caryocar brasiliense showed antimicrobial activity against the strains Stahylococcus aureus, Escherichia coli, Pseudmonas aeruginosa and Klebsiella pneumoniae, with susceptibility halos of 30mm, 33mm, 33mm and 34mm respectively. The sensitivity of S. aureus, E. coli, P. aeruginosa to Morinda citrifolia extract were 22mm, 8mm and 8mm. Therefore, the crude extract of Caryocar brasiliense showed antimicrobial activity against S. aureus, E. coli, P. aeruginosa and K. pneumoniae, and Morinda citrifolia was effective in inhibiting the growth of S. aureus, E. coli, P. aeruginosa.